(untitled) (Contemporary Mathematics, 2025)
This paper considers the two-dimensional Stokes system in a semi-infinite channel and is committed to deriving the structural stability of the model. Using the differential inequality technique, we obtain the expression of energy function. By making use of the earlier work, a second order differential inequality for energy function is obtained. By solving this second-order differential inequality, the continuous dependence on the coefficient of the system is established. This paper shows how to derive a priori estimates of nonlinear terms.